Comparison of the Performance of Broth Microdilution, Sensititre, and Two Different Automated Systems for Detecting Colistin Resistance Among Multidrug Resistant Acinetobacter baumannii Isolates - Aytac, Ozlem; Oner, Pinar; Senol, Feray Ferda; Asci-Toraman, Zulal (Doc Design Informatics Co Ltd, 2022)
Objectives: Although the broth microdilution method (BMD) is recommended in determining colistin resistance, the search for alternative methods continues. We aimed to determine the effectiveness in detecting colistin sensitivity by comparing the liquid microdilution method, which is the gold standard method for colistin susceptibility testing, and the SensititreT microdilution (Thermo Fisher Scientific, MA, USA), PhoenixT 100 (Becton Dickinson, USA), and MicroScan WalkAwayT (Beckman Coulter, USA) automated systems, which are the commercial BMD methods. Methods: For this purpose, 100 multidrug resistant strains of Acinetobacter baumanii were tested for colistin susceptibility. Antibiotic susceptibility results were compared with broth microdilution, SensititreT microdilution (Thermo Fisher Scientific, MA, USA), PhoenixT 100 (Becton Dickinson, USA), and MicroScan WalkawayT (Beckman Coulter, USA). Results: According to the criteria set by International Organization of Standardization (ISO), categorical agreement, major error, and very large error rates were not found in acceptable performance when the Phoenix and Sensitizer microdilution methods were compared with the gold standard method BMD. In addition, we determined that the categorical agreement (97%), major error (1%), and very large error (2%) rates of the MicroScan Walkaway method were acceptable. Conclusion: Since BMD is not a practical method, its use is not preferred. Simple and accurate phenotypic detection methods to determine colistin resistance in routine microbiology laboratories have not yet been defined. Although different results were obtained in different studies, MicroScan Walkaway provided the necessary criteria for the method acceptance in our study.
Klinik Örneklerden İzole Edilen Çoklu Dirençli Acinetobacter baumannii İzolatlarının Kolistin Direncinin Sıvı Mikrodilüsyon, Sensititre ve İki Farklı Otomatize Sistem ile Karşılaştırılması
Keywords: colistin; Acinetobacter baumannii; broth microdilution; sensititre; automated systems